2007
DOI: 10.1590/s0101-20612007000100013
|View full text |Cite
|
Sign up to set email alerts
|

Análise química de corpos de frutificação de Pleurotus sajor-caju cultivado em diferentes concentrações de nitrogênio

Abstract: 72 ResumoOs cogumelos do gênero Pleurotus normalmente crescem bem em substratos mais pobres em nitrogênio, ao contrário dos cogumelos Agaricus que requerem substratos com relação C/N mais estreita. Por outro lado, os valores nutricionais do cogumelo dependem da composição química do substrato utilizado e das condições de cultivo. Este trabalho teve como objetivo avaliar o teor de proteína dos corpos de frutificação do cogumelo Pleurotus sajor-caju cultivado em capim coast-cross, bagaço de cana-de-açúcar, farel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
0
5
1
3
Order By: Relevance
“…In our study, the nitrogen concentration (urea) inhibited inversely proportionally to the mycelial biomass growth of L. crinitus until complete inhibition. Silva et al (2007) reported that the nitrogen concentration of 20.0 g/L in the cultivation medium completely inhibited the mycelial biomass growth of Pleurotus sajor-caju, while in our study the concentration of 16.0 g/L inhibited 95.1% of the mycelial biomass growth. Valle et al (2014) reported that under optimal conditions for laccase activity with L. crinitus, the concentration of 2.8 g/L of nitrogen (urea) inhibited in 72% of the mycelial biomass growth in liquid cultivation.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In our study, the nitrogen concentration (urea) inhibited inversely proportionally to the mycelial biomass growth of L. crinitus until complete inhibition. Silva et al (2007) reported that the nitrogen concentration of 20.0 g/L in the cultivation medium completely inhibited the mycelial biomass growth of Pleurotus sajor-caju, while in our study the concentration of 16.0 g/L inhibited 95.1% of the mycelial biomass growth. Valle et al (2014) reported that under optimal conditions for laccase activity with L. crinitus, the concentration of 2.8 g/L of nitrogen (urea) inhibited in 72% of the mycelial biomass growth in liquid cultivation.…”
Section: Discussioncontrasting
confidence: 54%
“…Lentinus crinitus (L.) Fr. is a wild basidiomycete, native to Brazil, with pantropical (tropical regions of Africa, Asia and America) and neotropical (Central America, southern Florida, Caribbean islands and South America) distribution, frequently found in decomposing tree trunks (SILVA;GIBERTONI, 2006). This fungus grows in several substrates and is utilized in bioremediation (BALLAMINUT;MATHEUS, 2007), product discoloring in the textile industry (SANCHEZ-LOPEZ et al, 2008;NIEBISCH et al, 2010;ALMEIDA et al, 2018;MARIM et al, 2018) and presents a powerful arsenal of enzymes dedicated to the breakdown and consumption of lignocellulose (VALLE et al, 2014;CAMBRI et al, 2016;CONCEIÇÃO et al, 2017;SANTANA et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, há evidências de que o excesso de N mineral ou orgânico, além de exercer um efeito negativo sobre o crescimento micelial, pode inibir a síntese de enzimas que degradam a lignina (KIRK et al, 1978, SILVA et al, 2007GRACIOLLI et al, 2010).…”
Section: Substratosunclassified
“…foi totalmente inibido (SILVA et al, 2007). O início da formação de primórdios em diferentes substratos para o gênero Pleurotus tem sido observado entre 19º e 30º dias (KHANNA et al, 1992, RAGUNATHAN et al, 1996SWAMINATHAN, 2003, GRACIOLLI et al, 2008.…”
Section: Substratosunclassified
“…Yıldız, Gezer & Temiz, 2002;Silva, Dias, Siqueira, Schwan & 2007). Masarirambi, Mamba & Earnshaw (2011) suggested that mushroom cultivation is an alternative way of enhancing income level in developing countries due to its possibility of low cost of production, high profit and quick returns.…”
Section: Introductionmentioning
confidence: 99%